ChemInform Abstract: Coffinite, USiO4, Is Abundant in Nature: So Why Is It So Difficult to Synthesize?. Issue 39 (September 2015) - Mesbah, Adel; Szenknect, Stephanie; Clavier, Nicolas; Lozano‐Rodriguez, Janeth; Poinssot, Christophe; Den Auwer, Christophe; Ewing, Rodney C.; Dacheux, Nicolas
Abstract Conditions are established under which coffinite can be reproducibly synthesized.